Association of Air Pollution and Lung Function of Young Adult Females in New Delhi - Harshita Kelkar; Arun Kumar Sharma; Sanjay Chaturvedi (Journal of Health and Pollution, 2019)
Background. Lung function tests reflect the underlying physiological condition of the airways and the alveoli. Therefore, they help to evaluate the respiratory health of an individual. Lung functions are compromised far before appearance of the signs and symptoms of chronic respiratory diseases. Air pollution adversely affects lung function. Exposure to sources of pollution differ between men and women due to commuting and smoking habits. The present study was carried out in Delhi to assess the association of exposure to air pollution sources with lung function of young adult females, as this younger age group is expected to have a different exposure profile than older women. Methods. The present study was conducted on the campus of a central university in Delhi among 18- to 25-year old females (n=200). A pre-tested, close-ended and interviewer-administered questionnaire was used that consisted of information on sociodemographic details of the participants and self-reported exposure to air pollution sources at the residence of participants, during their commute to and from college, and at school. Both active and passive smoking status were recorded. Lung function was assessed using a digital spirometer. Results. A significant association was observed between percentage of predicted value of forced expiratory volume in one second (FEV1)/forced vital capacity (FVC) and peak expiratory flow (PEF) with the number of years the participant had resided in Delhi (p<0.05). Forced vital capacity and FEV1 of those using closed transport methods such as car, metro, and air-conditioned (A/C) bus were significantly better than those who used open transport methods such as non-A/C bus and scooter (p<0.05). Forced vital capacity and FEV1 were significantly decreased among those who had a smoke-producing factory in the vicinity of their residence (p<0.05). A significant decrease in FVC and FEV1 was observed among active smokers and among those who were exposed to passive smoking by family members in comparison to those who were not exposed (p<0.05). Conclusions. The results of the present study suggest that air pollution exposure plays a role in determining the lung function profile of young adult females. This study provides baseline data on lung function of young adult females which could be used in future longitudinal cohort studies. Participant Consent. Obtained Ethics Approval. The study was approved by the Institutional Ethics Committee of University College of Medical Sciences. Competing Interests. The authors declare no completing financial interests.